Any Indication for Bias due to Participation? Comparison of the Effects of a Parent Management Training Rated by Participating and Non‐Participating Parents. (24th February 2012) - Hautmann, Christopher; Hoijtink, Herbert; Eichelberger, Ilka; Görtz‐Dorten, Anja; Hanisch, Charlotte; Plück, Julia; Walter, Daniel; Döpfner, Manfred
<x xml:space="preserve">Abstract</x> Ratings of parents that have participated in a parent training for child externalizing behaviour problems might be biased (e.g., they may report symptom reduction to reward their own endeavours for attending the training). The potential for bias in parent ratings was investigated in a secondary analysis of an effectiveness study of a parent management training for children (aged 3–10 years) with externalizing behaviour problems under routine care conditions. For the 56 families included in the current analysis, we compared the ratings of training participants (predominately mothers) and training non‐participants (predominately fathers). A 3‐month waiting period prior to treatment served as the control condition. Outcome measures were attention problems and conduct problems of the children and perceived parental self‐efficacy rated by both the mothers and fathers. Child attention problems and conduct problems both decreased significantly during the treatment period for participating and non‐participating parents, and the changes in ratings during treatment were of a similar magnitude for participants compared with non‐participants. Taking into account the methodological limitations of the current analysis, no indication was found that treatment effects are strongly biased due to participation in the training. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Messages Previous positive findings of mothers' and fathers' ratings on parent management training for children with externalizing problem behaviour have mostly come from parents who also attended the training. For child behavioural problems, the results of the current analysis demonstrate similar perceived changes by parents who did and did not participate in the training. Our findings underscore the relevance and importance of parent ratings for treatment evaluation.